If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2z + -3) = 5(z + 2) Reorder the terms: 3(-3 + 2z) = 5(z + 2) (-3 * 3 + 2z * 3) = 5(z + 2) (-9 + 6z) = 5(z + 2) Reorder the terms: -9 + 6z = 5(2 + z) -9 + 6z = (2 * 5 + z * 5) -9 + 6z = (10 + 5z) Solving -9 + 6z = 10 + 5z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-5z' to each side of the equation. -9 + 6z + -5z = 10 + 5z + -5z Combine like terms: 6z + -5z = 1z -9 + 1z = 10 + 5z + -5z Combine like terms: 5z + -5z = 0 -9 + 1z = 10 + 0 -9 + 1z = 10 Add '9' to each side of the equation. -9 + 9 + 1z = 10 + 9 Combine like terms: -9 + 9 = 0 0 + 1z = 10 + 9 1z = 10 + 9 Combine like terms: 10 + 9 = 19 1z = 19 Divide each side by '1'. z = 19 Simplifying z = 19
| 2(9x)+2(2x)=484 | | 7(5x+13)=301 | | 2/3x=-1/2 | | 3w+4+2w=-26 | | (1)/(5p2)*(5p3-35p2)/(9p-36) | | X(2)+2x=23 | | 5x+2=9x-22 | | w/7+2=5 | | 5(-9x+15)=-195 | | x=450-.5y | | 3k+16=5 | | 7x^-3/16x^-1 | | 5(-9+15)=-195 | | x+(s+40)=180 | | 4x+2(3x-7)=6-(4-x) | | 3(6m)+m=21m | | 7(5x+16)=-203 | | 12y-7=53 | | -26x-2x=10-8x | | 4x^2+-10x+25=0 | | 2(x)+y=900 | | 10(-10x+12)=-380 | | 4x^2-10x+25=20 | | 5x^2-20=4 | | (5x+15)/(3x+9) | | 5x+15/3x+9 | | 3/7=x | | -5(9x+12)=-375 | | 1x-11x+8=88 | | (2x^2+3x-4)-(4x^2-7x+1)= | | a*a-5a=-4 | | 13=-3x-14 |